Efforts to Improve Early Childhood Cognitive Abilities Through Virtual Realty (VR) Based Learning Media - Septyani, Deli; Pradana, Pascalian Hadi; Hasanah, Hisbiyatul (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
The development of technology in this millennial era is giving a new face to education. Issues were found from the observations, including: 1) a lack of technological facilities in schools, 2) a decline in children's cognitive abilities. Based on the issues presented in the background, this study aims to use virtual reality learning media to enhance the cognitive abilities of early childhood children. Classroom Action Research (CAR), the method used in this research. To collect data, the researchers used the following data collection methods: 1) Observation, gathering information from the observation of the research subjects. 2) Documentation, collecting several images of activities as part of the research. The author uses quantitative and qualitative analysis methods to collect data. This research found that the use of virtual reality-based media as a learning tool can enhance the cognitive abilities of young children. It can be seen from the first cycle of research that the classical average score of the children reached 54%. Meanwhile, in the second cycle, it increased to 82%. The target for the classical achievement set by the researcher was an average of 78%. Thus, in the second cycle, the classical average score of the children was achieved in accordance with the researcher's target. The use of virtual reality (VR) media has brought new innovations to the world of early childhood education, although currently only a few schools are using it for learning.